The wicked problem of employee wellbeing: creating safe space within a change laboratory. (4th May 2021) - Lawless, Aileen; Willocks, Katie Elizabeth
ABSTRACT: This article sheds light on employee wellbeing. We reveal how an 'adapted' action learning intervention (a change laboratory) introduced prior to the Covid-19 pandemic in the UK, enabled learning and action to emerge within an educational programme. We utilise the theoretical lens of activity theory to illustrate the challenges and tensions of promoting and sustaining an employee wellbeing agenda. Follow-up questioning (Q) of key informants, using the insights (P – programmed knowledge) generated during the change laboratory provide evidence of learning (L). This provides insight into the learning and action that occured after the initial intervention. We explore employee wellbeing from a socio-cultural perspective and illustrate how action and learning are intertwined to produce goal-oriented outcomes. This socio-cultural perspective contributes to the theory of action learning by illuminating how activity is mediated by cultural means, the rules and tools operating in an activity system. This perspective provides a focus upon learning and agency in the workplace and supports a more complicated understanding of 'wicked problems', viewed as the challenges and tensions which emerge in practice as break-downs, clashes or problems. We argue that these spaces must be protected if employee wellbeing is to become, and remain, integrated within an organisation activity system.